EKSPRESI METAFORIS DALAM PUISI-PUISI MARDI LUHUNG - Tsalits Abdul Aziz Al farisi (LPPM UNISDA, 2021)
This research aims to explore poem based on Michael Halley's space of metaphorical expression. It consistof nine metaphor category: human, animate, living, terrestrial, substance, energy, cosmic, being. Meanwhile, based on philosophic, there are etos, logos, and patos. The theory space of metaphorical expression Michael Halley is used on this. It says, hierarchy of human perception regarding space, start on his/her own perception. Because human and his/her action reflect the interaction with environment. That interaction is explained on metaphor. Meanwhile, the philosophic poin of the methaphor is about life. The message of life comes from the analysis of whole meaning, start on the explisit meaning or outside structure to the inplicit one. To find out the meaning, this research uses Friedrich Schleirmacher's hermeneutic and Pierce Semiotic approach. Those two theory support each other to analyze poem which consist of symbol and metaphor. This research uses analysis descriptive method. It describes the facts then analyzes those directly. On Mardi Luhung poems, researcher describes facts which form diction. After that, the diction which consist of metaphor is analyzed by observing the philosophic meaning. The result, the poet often to use methaphor which relate on space perception, in human category. This is the way to express his idea through poems. He uses nature symbols, animals, and myth, those have metaphoric and symbolic meaning as the way to express idea through poems.